Análise dos custos diretos das rotas de veículos de cargas do Distrito Industrial considerando o Rodoanel Viário de Manaus. - Angiolis, Aline Cruz de (Brasil, 2022)
The comparative analysis of the operational costs of freight vehicles on urban routes is necessary, since transportation costs are a significant part in determining the final price of a product or service and determines the profitability of the activity. Knowing this, companies seek ways to minimize their transportation costs in order to offer the user a product with a competitive price to the final customer and profitable to the offering company. Through vehicle routing and route analysis methods it is possible to approximate the real environment in order to fulfill the objective of this monograph, which was to performe a comparative analysis of the operational costs between two routes used by cargo vehicles in urban areas of Manaus, considering the Manaus Beltway, which is under construction. For this, the studied routes were identified, besides collecting operational and cost data about the cargo transportation on the selected routes for comparison and comparative analysis of operational costs by cargo vehicles operating in Manaus' Industrial District and the new Beltway under construction. The comparison was done from the vehicle routing and its costs, being chosen the most adequate method to the situation to make possible the analysis regarding the best option between the selected routes for such comparison. The methods used were the Time Dependent Vehicle Routing Problem (PRVDT) and the Clarke & Wright Method. The routes had as origin the Centro Cultural dos Povos da Amazônia, located at Distrito Industrial I, 2222 Silves Avenue, Manaus, AM 69073- 270 and destination the International Airport Eduardo Gomes, 1350 Santos Dumont Avenue, Manaus, AM 69041-000, one of routes through Rodrigo Otávio Avenue and the other one through the Manaus Beltway, besides the use of a viability map for the use of each route departing from different origins. At the end of the comparison, it was concluded that both by the PRVDT and the Clarke & Wright Method, the route with the lowest costs was the Rodrigo Otávio Avenue route, having its time, mileage traveled, fuel used, both considering flat and hilly routes, lower than the Manaus Beltway route. Such result was obtained by the starting point adopted, and it can be different if different starting points are considered, as is the case of leaving the Brasileirinho 230 kV Substation, the most economical route will then be the Manaus Beltway, as well as leaving Gree do Brasil, one can use both the Rodrigo Otávio Avenue route and the Manaus Beltway route.